2018
DOI: 10.3390/toxins10120495
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Neurotoxins (BoNTs)—Antibody and Vaccine

Abstract: Botulism, caused by exposure to one or more of the eight serotypes of botulinum neurotoxins (BoNTs) (BoNT/A through H), is often fatal without rapid treatment. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Their production is highly reproducible compared to animal hyperimmune sera thereby preventing batch to batch variations in antibody affinity 50 . Over the last decade, several neutralizing mAbs against the distinct BoNT types have been generated 17,18,54 . However, mAbs are specific of single epitopes only and extended protective coverage most often requires the combination of several mAbs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their production is highly reproducible compared to animal hyperimmune sera thereby preventing batch to batch variations in antibody affinity 50 . Over the last decade, several neutralizing mAbs against the distinct BoNT types have been generated 17,18,54 . However, mAbs are specific of single epitopes only and extended protective coverage most often requires the combination of several mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…50 Over the last decade, several neutralizing mAbs against the distinct BoNT types have been generated. 17,18,54 However, mAbs are specific of single epitopes only and extended protective coverage most often requires the combination of several mAbs. For example, the association of three distinct mAbs targeting F I G U R E 2 TA12 blocks BoNT/A1 binding to SV2C-LD by targeting a common area on H C A1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, in order to circumvent this problem several other serotypes of BTX than BTX-A or BTX-B have been explored as potential therapeutic agents in humans. BTX-E and BTX-F seem to be alternative serotypes in patients who had become resistant to BTX-A and found to be effective in dystonic patients (44,60,61).…”
Section: Antibody Development Against Botulinum Toxinmentioning
confidence: 99%
“…A novel vaccine-design strategy has been developed using the nontoxic recombinant domains of BoNTs as antigens, but not the full toxin. 11 , 12 Previous animal studies have demonstrated that the HC domains are nontoxic, and sufficient to generate a protective immune response against natural BoNTs. Besides, the recombinant Hc fragments can be synthesized in large quantities, and are less hazardous than traditional toxin-inactivated vaccines.…”
Section: Introductionmentioning
confidence: 99%